A Proof-Based Account of Legal Exceptions. - Duarte d’Almeida, Luís (Oxford Journal of Legal Studies)
I propose and defend a proof-based account of legal exceptions. The basic thought is that the characteristic behaviour of exceptions is to be explained in terms of the distinction, relative to some given decision-type C in some decision-making context, between two classes of relevant facts: those that may, and those that may not, remain uncertain if a token decision C is to count as correctly made. The former is the class of exceptions. A fact F is an exception relative to some decision-type C, I claim, if (i) the ascertainment of F is sufficient for a token decision C not to count as correctly made, and (ii) the ascertainment of the negation of F is not necessary for a token decision C to count as correctly made. I also recuperate, reconstruct and discuss some of HLA Hart’s early views on defeasible judicial decisions. These two projects are closely connected: the latter is a vehicle for the former.